2017
DOI: 10.1051/0004-6361/201730525
|View full text |Cite
|
Sign up to set email alerts
|

The long-term evolution of known resonant trans-Neptunian objects

Abstract: Aims. Numerous trans-Neptunian objects are known to be in mean-motion resonance with Neptune. We aim to describe their longterm orbital evolution (both past and future) by means of a one-degree-of-freedom secular model. In this paper, we focus only on objects with a semi-major axis larger than 50 astronomical units (au). Methods. For each resonant object considered, a 500 000-year numerical integration is performed. The output is digitally filtered to get the parameters of the resonant secular model. Their lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…resonant KBOs have been identified in the a > 100 AU region, i.e., 2004 PB 112 in the 5:27 resonance (Saillenfest & Lari 2017), 2015 KE 172 , and 2007 TC 433 in the 1:9 resonance (Volk et al 2018); these KBOs are in our sample.…”
Section: Real Kbosmentioning
confidence: 68%
See 1 more Smart Citation
“…resonant KBOs have been identified in the a > 100 AU region, i.e., 2004 PB 112 in the 5:27 resonance (Saillenfest & Lari 2017), 2015 KE 172 , and 2007 TC 433 in the 1:9 resonance (Volk et al 2018); these KBOs are in our sample.…”
Section: Real Kbosmentioning
confidence: 68%
“…The agreement between our numerical and theoretical approaches suggests that the weak highorder resonances in the distant Kuiper belt could have little impact on the mean plane determination. As a matter of fact, Saillenfest & Lari (2017) found that, for the majority of resonant KBOs with a > 50 AU, their secular behaviors can hardly be affected by mean motion resonances. Up to now, only three 1 http://www.minorplanetcenter.net/iau/lists/TNOs.html Fig.…”
Section: Real Kbosmentioning
confidence: 99%
“…( 3.3) has one degree of freedom, and the solutions follow its level curves in the (U, u)-plane. This secular model has been successfully used by Saillenfest et al (2016Saillenfest et al ( , 2017; Saillenfest and Lari (2017) to study the long-term evolution of distant resonant trans-Neptunian objects (TNOs), for which the ratio ξ is of the order of 10 −4 . However, NEOs evolve on a much shorter timescale than TNOs, and the condition in Eq.…”
Section: Adiabatic Approximationmentioning
confidence: 99%
“…Starting from the theory of Gronchi and Milani (2001), we need to keep resonant harmonics in the Hamiltonian by semi-averaging techniques, and the method must remain valid for arbitrary eccentricities and inclinations. Semi-averaged theories have been widely used in the past for describing the long-term orbital dynamics of resonant small bodies (see e.g Wisdom, 1985;Moons and Morbidelli, 1995;Milani and Baccili, 1998;Saillenfest et al, 2016Saillenfest et al, , 2017Sidorenko, 2006Sidorenko, , 2018Sidorenko, , 2020. Our aim is to combine such a method with the model of Gronchi and Milani (2001) to compute proper elements of resonant NEOs.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the orbital elements have a very smooth, quasi-integrable, long-term evolution that can be studied by analytical (or semi-analytical) means. We will recall here the method proposed by Henrard (1990Henrard ( , 1993 and applied to the trans-Neptunian region by Saillenfest et al (2016Saillenfest et al ( , 2017b and Saillenfest and Lari (2017). We will also discuss its variant introduced independently by Wisdom (1985) and used for instance by Sidorenko (2006Sidorenko ( , 2018.…”
Section: Mean-motion Resonances With the Giant Planetsmentioning
confidence: 99%